Phenotypic and Genotypic Characterization of Macrolide, Lincosamide and Streptogramin B Resistance among Clinical Methicillin-Resistant Staphylococcus aureus Isolates in Chile - Mario Quezada-Aguiluz; Alejandro Aguayo-Reyes; Cinthia Carrasco; Daniela Mejías; Pamela Saavedra; Sergio Mella-Montecinos; Andrés Opazo-Capurro; Helia Bello-Toledo; José M. Munita; Juan C. Hormazábal; Gerardo González-Rocha (MDPI AG, 2022)
Macrolides, lincosamides, and type B streptogramins (MLSB) are important therapeutic options to treat methicillin-resistant Staphylococcus aureus (MRSA) infections; however, resistance to these antibiotics has been emerging. In Chile, data on the MLSB resistance phenotypes are scarce in both community-(CA) and hospital-acquired (HA) MRSA isolates. Antimicrobial susceptibility to MLSB was determined for sixty-eight non-repetitive isolates of each HA-(32) and CA-MRSA (36). Detection of SCCmec elements, ermA, ermB, ermC, and msrA genes was performed by PCR. The predominant clones were SCCmec I-ST5 (HA-MRSA) and type IVc-ST8 (CA-MRSA). Most of the HA-MRSA isolates (97%) showed resistance to clindamycin, erythromycin, azithromycin, and clarithromycin. Among CA-MRSA isolates, 28% were resistant to erythromycin, azithromycin, and 25% to clarithromycin. All isolates were susceptible to linezolid, vancomycin, daptomycin and trimethoprim/sulfamethoxazole, and over 97% to rifampicin. The ermA gene was amplified in 88% of HA-MRSA and 17% of CA-MRSA isolates (p < 0.001). The ermC gene was detected in 6% of HA-SARM and none of CA-SARM isolates, whereas the msrA gene was only amplified in 22% of CA-MRSA (p < 0.005). Our results demonstrate the prevalence of the cMLSB resistance phenotype in all HA-MRSA isolates in Chile, with the ermA being the predominant gene identified among these isolates.